Indonesia and the Rohingya crisis: An analysis of the role of transit countries in refugee protection - Jumadi, Joko (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This article examines Indonesia's role as a transit country in handling Rohingya refugees fleeing violence and persecution in Myanmar. On the other hand, this study also highlights ad hoc policies and humanitarian practices carried out by the central government, local governments, international organizations, and local communities in Aceh in accommodating and assisting Rohingya refugees. Methods: Using a normative legal approach and policy analysis, this study evaluates Indonesia's national legal framework which does not specifically regulate refugee status, thus creating challenges in providing long-term protection. Findings: The results of the study show that although Indonesia is not a party to the 1951 Refugee Convention, the principle of non-refoulement and the value of human solidarity have been the basis of a relatively consistent temporary policy. Conclusion: This article recommends the need to strengthen national regulations, multi-party coordination mechanisms, and increase the capacity of related institutions so that Indonesia can carry out its role as a transit country more effectively, humanely, and in line with human rights principles. Novelty/Originality of this article: This study offers a comprehensive analysis of Indonesia's role as a transit country in handling Rohingya refugees, which has previously been rarely studied in depth from a national legal and policy perspective. This study also raises the importance of integrating the principle of non-refoulement into domestic regulations as an innovation in more sustainable refugee protection policies.